The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1016/j.phrp.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Dental Procedures, Oral Practices, and Associated Anxiety: A Study on Late-teenagers

Abstract: ObjectivesThe study aims to determine the degree of anxiety pertaining to dental procedures and various oral hygiene practices among college teenagers.MethodsCorah's Modified Dental Anxiety Scale was administered on a randomly chosen sample of 100 Indian college students (50 males and 50 females) of Delhi University, belonging to the age group of 17–20 years.ResultsDescriptive statistical computations revealed 12.14 years as the mean age of first dental visit, with moderately high levels of anxiety (60.75%) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
5
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 40 publications
(45 reference statements)
3
29
5
3
Order By: Relevance
“…The research into oral hygiene habits showed that most participants maintained good oral health and had regular dental check-ups. These results differ from previous studies showing that the adolescents irregularly visit dentists, i.e., only when there is a problem 11,20,21 . The difference in these results may be due to the differences in the sample because the authors focused on the rural population of a lower socioeconomic status.…”
Section: Discussioncontrasting
confidence: 99%
“…The research into oral hygiene habits showed that most participants maintained good oral health and had regular dental check-ups. These results differ from previous studies showing that the adolescents irregularly visit dentists, i.e., only when there is a problem 11,20,21 . The difference in these results may be due to the differences in the sample because the authors focused on the rural population of a lower socioeconomic status.…”
Section: Discussioncontrasting
confidence: 99%
“…This disagreement in the dental status and the subjects' self-evaluation of oral health habits could be explained in two ways: the influence of popular culture and mass media, or the desire to answer the questions in a more acceptable way. Our data about oral hygiene habits differ from similar studies [30,31], which showed that adolescents did not visit their dentists regularly. In part, this discrepancy could be explained by the rural nature of their study population, which had limited access to dental care.…”
Section: Discussioncontrasting
confidence: 99%
“…Contradictory to the previous findings regarding tooth loss and normative treatment needs [30,31], the subjects in our study reported good oral hygiene habits with 99.2% brushing twice a day. This disagreement in the dental status and the subjects' self-evaluation of oral health habits could be explained in two ways: the influence of popular culture and mass media, or the desire to answer the questions in a more acceptable way.…”
Section: Discussionsupporting
confidence: 56%
“…To explain the association between dental fear and level of caries, the understanding of the dental fear's cycle is essential. Dental fear leads to the avoidance of dental visit, which consequently contributes to poorer dental health, thus, these individuals often make dental appointments for more invasive treatment or emergency reasons, contributing to the increase of dental fear (21). Evaluating the non-use of dental services, Goettems et al (22) observed that around ¼ of the surveyed children had never visited the dentist and the prevalence of non-use was 62% higher in children who were afraid.…”
Section: Discussionmentioning
confidence: 99%